(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2022)
The article records a survey on the state of the art of research in Media Communication in Paraguay. In the first section, there is a historical research of the Paraguayan educational context, followed by a reflection on two Paraguayan researchers and the approaches from which they consider Communication. The third section presents an investigation conducted in four Paraguayan scientific journals with online access. It is possible to verify that there is scarce bibliography, besides having few references to Paraguay in scientific journals and other national bibliographical works published there. The political context is pointed out as a probable origin on the academic invisibility of Communication studies.